KALIMAT SEMATAN PADA TEKS TERJEMAHAN ALQURAN YANG MENGANDUNG ETIKA BERBAHASA - Shofiyuddin . (Sasindo, 2014)
This study has three objectives. (1) Identify the type of transformation embedded. (2) Describe the process of transformation embedded. (3) Describe the transformation rules found in the translated text of the Qur'an containing ethics speak. Data collected by technical documentation, see, and record. The data in this study in the form of sentences that are contained in the translation of the verses of the Qur'an that contain language in which ethics are embedded transformation. Data source is the translated text of the Qur'an containing ethics speak. Analysis of the data in this study using a unified method ekstralingual and intralingual match. Testing the validity of the data using triangulation techniques of data sources. Results of the study: first, there are four types of transformation embedded contained in the translated text of the Qur'an containing ethics speaking, the relative clause (there are 41), substitute noun phrases (No 7), substitute verb phrase (there are two) and substitute the phrase adjective ( there are 2). Second, the process of transformation embedded in the translated text of the Qur'an containing ethical language occurs at the beginning (there are 10), middle (there are 3), the end (there are 11), the start-end (no 3), middle-end (no 3), the end being surrounded (No 3), and the beginning-middle-end (no 3). Third, the transformation rules based on the type of sentence is divided into two, namely the complex sentences and simple sentences. Complex sentences consisting of more than one transformation process and results in the formation:-Sematan Sematan (No 1), Sematan-density (there are 10), density-Sematan (there are 11), density-Sematan-density (No 3), Sematan-Rapatan- Embeds (No 3), density-density-embedded-embedded (no 4), embedded-density-embedded-density (No 3), embedded-density-density-embedded-embedded (no 2), embedded-density-Sematan- -density-Sapatan-Sematan Sematan (No 1). Simple sentence consists of only one course and the process of transformation in this study contained 10 sentences.Keywords: embedded sentence, the translated text of the Qur'an, ethics speak.